The sibling - Sutton - Smith, Brian; Rosenberg, B (New York: Holt, Rinehart and Winston, 1970)
Contents: The sibling romance. Some precautions. Sex status effects. Academic primogeniture. Affiliation and conformity. Developmental transormations of dependency and archivement. Hierarchical and egalitarian interactions. Consistencies and transformations in sibling status
Includes bibliographical references and index
Keywords: Familia - Sociología Familiar